POSISI STRATEGIS KEPALA SEKOLAH DALAM MEMBANGUN MANAJEMEN KESISWAAN DAN SDM DI LEMBAGA PENDIDIKAN ISLAM MODERN - Fikria Aulia, Farina; Fadla Robbi; Muhamad Yasin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Modern Islamic educational institutions face complex challenges in the era of globalization and digitalization that demand professional and value-based institutional management. This study aims to examine the strategic position of school principals in developing student management and human resource management (HRM) in modern Islamic educational institutions through a library research approach. The findings reveal three main conclusions: first, school principals possess a multidimensional EMASLIM role grounded in Islamic values such as amanah, adalah, and syura; second, effective student management encompasses a holistic student affairs cycle integrating tarbiyah and ta'lim values at every stage; third, optimal HRM requires a comprehensive management cycle encompassing recruitment, competency development, academic supervision, and value-based performance evaluation. This study concludes that the integration of strategic principal leadership, structured student management, and value-based HRM constitutes an inseparable unified system in realizing modern Islamic educational institutions that are excellent and globally competitive.